Higher education governance: Perceptions of rectors, council of higher education members, and government representatives - Akbulut, Meltem. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
This qualitative study investigates the operation of the system governance model in Turkish higher education through the perceptions of state university rectors, Council of Higher Education (CoHE) members, and government representatives. It also examines the advantages and the challenges of this model and explores the suggestions for improvements in the model. The study is based on semi-structured interviews with fifteen rectors, twelve CoHE members, and four government representatives and informed by grounded theory. The data analysis is conducted under the conceptual framework that is derived from the literature review and coined as “Rhizomatic System Governance Process Framework.” Based on the findings, the structure operating in the system governance model appears to be law-bound, have power-centers, combine supervision of inputs and outputs, and deprofessionalize academic roles. Also, a suggestion for a pluralized coordination seems to indicate perception of system governance as a process, which is argued to be “Rhizomatic-Tree-like” in this study. The main contribution of this study to the literature is the development of the “Rhizomatic System Governance Process Framework” by taking a deconstructive and reconstructive perspective in the literature review. Although the sub-items in the framework can change from one context to another, the main items together with their sub-items as a whole can offer a new perspective in the study of the system governance of higher education.
Keywords: Higher education and state -- Turkey.; Universities and colleges -- Turkey.